The Mecistocephalidae of the Japanese and Taiwanese islands (Chilopoda: Geophilomorpha) - Uliana, Marco; Bonato, Lucio; Minelli, Alessandro (Zootaxa, 2007)
We present a comprehensive taxonomic revision of the Mecistocephalidae occurring in the Japanese main archipelago and in Taiwan, based on both the critical analysis of published information and the comparative morphological examination of representative specimens, including type material. A total of 34 species in 8 genera are recognised. Diagnostic characters, synonyms and geographical distribution are reviewed and discussed for all species, and a detailed redescription is provided for 12 already known species. An identification key to all species is also provided. The following species are described as new: Arrup ishiianus, Arrup lilliputianus, Arrup longicalix, Arrup kyushuensis, Mecistocephalus changi, Mecistocephalus karasawai. The following synonymies are new: Tygarrup monoporus Shinohara, 1961 = Dicellophilus pulcher (Kishida, 1928); Mecistocephalus fenestratus Verhoeff, 1934 = Mecistocephalus japonicus Meinert, 1886; Mecistocephalus insulomontanus Gressitt, 1941 = Mecistocephalus marmoratus Verhoeff, 1934; Mecistocephalus manazurensis Shinohara, 1961 = Mecistocephalus nannocornis Chamberlin, 1920; Mecistocephalus mirandus Pocock, 1895 = Mecistocephalus japonicus Meinert, 1886; Mecistocephalus okinawaensis Takakuwa, 1939 = Mecistocephalus pauroporus Takakuwa, 1936; Mecistocephalus takakuwai Verhoeff, 1934 = Mecistocephalus diversisternus (Silvestri, 1919). Dicellophilus pulcher (Kishida, 1928) new comb. is here recognised as the valid name for the species previously referred to as Dicellophilus latifrons Takakuwa,1934.